Drivers of successful common-pool resource management: A conjoint experiment on groundwater management in Brazil. (May 2022) - Cooperman, Alicia; McLarty, Alexandra R.; Seim, Brigitte
Highlights: A conjoint experiment assesses effective features of a groundwater governance system. Study conducted with rural residents in semi-arid Ceará state in Northeast Brazil. Community discussion, rules and penalties most effective for individual conservation. Social sanctions, resource monitoring most effective for collective management. Pictograms expand the method to low-literacy areas needing resource management. Abstract: Carefully designed common-pool resource (CPR) management systems can improve water security, but many NGOs and governments do not have the resources and logistical capacity to implement all important features of a system at once. In addition, users' perception of management features is important to increase buy-in and adoption of a new system. Which aspects of a commons management system do users perceive to be most important? We conduct a conjoint survey experiment about groundwater management with rural residents in the semi-arid region of Northeast Brazil. We randomly vary five features of a water management system: 1) discussion, 2) social sanctions for overuse, 3) rules and penalties, 4) payment, 5) monitoring and dissemination of conditions to users. Each feature increases perceived likelihood of collective well management and individual water conservation. We find that features act as complements or substitutes; in particular, discussion complements monitoring, and payment substitutes for rules. Our results have implications for how to study and prioritize the features of CPR management systems to improve water security in other rural, semi-arid regions with groundwater reliance when it is infeasible to implement all recommended features.